Coronavirus (COVID-19), Coagulation, and Exercise: Interactions That May Influence Health Outcomes - Zadow, Emma Kate; Wundersitz, Daniel William Taylor; Hughes, Diane Louise; Adams, Murray John; Kingsley, Michael Ian Charles; Blacklock, Hilary Anne; Wu, Sam Shi Xuan; Benson, Amanda Clare; Dutheil, Frédéric; Gordon, Brett Ashley (Seminars in Thrombosis and Hemostasis, 2020)
The proinflammatory cytokine storm associated with coronavirus disease 2019 (COVID-19) negatively affects the hematological system, leading to coagulation activation and endothelial dysfunction and thereby increasing the risk of venous and arterial thrombosis. Coagulopathy has been reported as associated with mortality in people with COVID-19 and is partially reflected by enhanced D-dimer levels. Poor vascular health, which is associated with the cardiometabolic health conditions frequently reported in people with severer forms of COVID-19, might exacerbate the risk of coagulopathy and mortality. Sedentary lifestyles might also contribute to the development of coagulopathy, and physical activity participation has been inherently lowered due to at-home regulations established to slow the spread of this highly infectious disease. It is possible that COVID-19, coagulation, and reduced physical activity may contribute to generate a “perfect storm,” where each fuels the other and potentially increases mortality risk. Several pharmaceutical agents are being explored to treat COVID-19, but potential negative consequences are associated with their use. Exercise is known to mitigate many of the identified side effects from the pharmaceutical agents being trialled but has not yet been considered as part of management for COVID-19. From the limited available evidence in people with cardiometabolic health conditions, low- to moderate-intensity exercise might have the potential to positively influence biochemical markers of coagulopathy, whereas high-intensity exercise is likely to increase thrombotic risk. Therefore, low- to moderate-intensity exercise could be an adjuvant therapy for people with mild-to-moderate COVID-19 and reduce the risk of developing severe symptoms of illness that are associated with enhanced mortality.
Keywords: coronavirus; pharmaceutical medications; coagulation; fibrinolysis; physical activity